Thymic Involution and Altered Naive CD4 T Cell Homeostasis in Neuromyelitis Optica Spectrum Disorder - Chang, Haoxiao; Cong, Hengri; Wang, Huabing; Du, Li; Tian, De-Cai; Ma, Yuetao; Xu, Yun; Wang, Yupeng; Yin, Linlin; Zhang, Xinghu (Frontiers in Immunology, 2021)
Circulating T helper cells with a type 17-polarized phenotype (TH17) and expansion of aquaporin-4 (AQP4)-specific T cells are frequently observed in patients with neuromyelitis optica spectrum disorder (NMOSD). However, naive T cell populations, which give rise to T helper cells, and the primary site of T cell maturation, namely the thymus, have not been studied in these patients. Here, we report the alterations of naive CD4 T cell homeostasis and the changes in thymic characteristics in NMOSD patients. Flow cytometry was performed to investigate the naive CD4+ T cell subpopulations in 44 NMOSD patients and 21 healthy controls (HC). On immunological evaluation, NMOSD patients exhibited increased counts of CD31+thymic naive CD4+ T cells and CD31-cental naive CD4+ T cells along with significantly higher fraction and absolute counts of peripheral blood CD45RA+ CD62L+ naive CD4+ T cells. Chest computed tomography (CT) images of 60 NMOSD patients and 65 HCs were retrospectively reviewed to characterize the thymus in NMOSD. Thymus gland of NMOSD patients exhibited unique morphological characteristics with respect to size, shape, and density. NMOSD patients showed exacerbated age-dependent thymus involution than HC, which showed a significant association with disease duration. These findings broaden our understanding of the immunological mechanisms that drive severe disease in NMOSD.